The scotopic low-frequency spatial contrast sensitivity develops in children between the ages of 5 and 14 years - Benedek, György; Benedek, Krisztina; Kéri, Szabolcs; Janáky, Márta (Neuroscience letters, 2003)
The purpose of this study was to investigate the development of visual contrast sensitivity (CS) in children between 5 and 14 years of age. Six spatial frequencies and static (0 Hz) and dynamic (8 Hz) conditions were used at photopic and scotopic luminance levels. The results revealed significant maturation of CS, which reached the adult-like values by 11–12 years of age. The development was more pronounced at low spatial frequencies (<2 cycles/degree) and in the dynamic condition. The scotopic CS exhibited slower development than the photopic CS. These results suggest the late maturation of the magnocellular visual pathway.